Comparative study of various models for hydrogen sulfide degradation in a biological packed tower - Tengkiat, Andrew Benedict (Animo Repository, 1999)
The study aims to find a suitable model for the treatment of hydrogen sulfide (H2S) gas in a packed tower with the immobilized bacteria Thiobacillus thioparus DW44. Four existing models were tested in the study, namely the following: 1. Pseudo-homogeneous Model, 2. Shell Balance Model, 3. Deep Biofilm Model, and 4. Dispersion Model. Modifications like changing the reaction rate kinetics from 0th or 1st order kinetics to purely Monod kinetics were made. The pseudo-homogeneous and dispersion models were applied to biological systems for the first time since it is commonly used in modeling chemical reaction systems only. Pseudo-homogeneous model is the model to be used for this system based on the analysis of residuals and PRESS (Predicted Sum of Squares) values of the different models. Deep biofilm model is quite suitable but the validity is somewhat doubtful due to the fact that the effective biofilm surface area on the packings is unknown.